PENINGKATAN HASIL BELAJAR KPK DAN FPB MELALUI PENELITIAN TINDAKAN KELAS MENGGUNAKAN MEDIA LAB MAYA KELAS V SD NEGERI 200508 PADANGSIDIMPUAN - Hasibuan, Barumun Parulian; Fujiwaty; Almira Amir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes of students on the topic of Least Common Multiple (LCM) and Greatest Common Factor (GCF) in the fifth grade of SD Negeri 200508 Padangsidimpuan, which was caused by the lack of use of interactive learning media. The purpose of this study was to improve students’ learning outcomes through the implementation of Lab Maya media in Classroom Action Research (CAR). The method used was Classroom Action Research with a cyclical model consisting of planning, implementation, observation, and reflection, conducted in two cycles. The subjects of the study were 22 fifth-grade students. Data were collected through learning outcome tests, student activity observation sheets, and documentation. The results of the study showed that the use of Lab Maya media was able to improve students’ learning outcomes, as indicated by the increase in the percentage of learning mastery from 45.5% in Cycle I to 86.4% in Cycle II. In addition, student activity and engagement in the learning process also increased significantly. The conclusion of this study is that Lab Maya media is effective in improving learning outcomes on LCM and GCF material. The implication of this study indicates that the use of technology-based interactive media can serve as an innovative alternative in mathematics learning at the elementary school level.